(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
A transverse descriptive study was carried out, according to the classification of therapeutic compliance, to evaluate adherence in 250 patients with a diagnosis of Heart Failure, registered with the health department of the municipality of Santiago de Cuba in 2009. The sample characterization was studied, with an assessment of adherence level and possible associated factors for sex, age and toxic habits. As an instrument for the work, data extraction was scheduled and the interview was carried out at patients' homes; the results were expressed in percentage and level of influence for associated factors. This was determined using the chi-square test. In the investigated population, adherence was greater for females, for age group 67-82 years, and toxic habits were found to have prevalence. Prevailing pharmacoterapies were digoxin, chlortalidone, captopril and isosorbide dinitrate, and a high level of adherence was found, both for the pharmacological and non-pharmacological treatments, in the studied sample. A good level of therapeutic adherence was found for 63.6% of the patients, regular level of adherence was found for 32% and only 4.4% or patients presented with poor adherence. Influencing factors were: knowledge of the treatment, number of medications, frequency of administration, and satisfaction with the service of pharmaceutical care.